2022
DOI: 10.3390/ijerph191912658
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the Homestead: Examining the Role of Relative Deprivation, Social Trust, and Urban Integration among Rural Farmers in China

Abstract: Actively promoting the orderly and voluntary withdrawal of idle rural house bases and effectively activating “sleeping” land assets are considered important measures to accelerate the modernization of agriculture and rural areas, as well as promoting the integrated development of urban and rural areas. However, few studies have focused on the superimposed effects of negative psychological and social environmental factors on the willingness of farmers to withdraw from their homestead. Therefore, we conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…There is a direct link effect between farmers' willingness to withdraw from contracted land and their willingness to withdraw from the homestead. The outcomes are parallel with the assumption by Si et al [31]. However, in a study of Jinhu County, Jiangsu Province, China, Zhao et al [34] found distinctive outcomes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…There is a direct link effect between farmers' willingness to withdraw from contracted land and their willingness to withdraw from the homestead. The outcomes are parallel with the assumption by Si et al [31]. However, in a study of Jinhu County, Jiangsu Province, China, Zhao et al [34] found distinctive outcomes.…”
Section: Discussionsupporting
confidence: 68%
“…Many necessary decision-making plans and major strategies at the decision-making level emphasize that the withdrawal of rural land must respect farmers' wishes and allow them to make their own choices [29]. For this reason, relevant studies (such as Liu et al [30], Chen et al [12], and Si et al [31]) have focused on the willingness of farmers to withdraw from their land and studied that under the background of urbanization and non-agriculture employment. Where farmers have the characteristics of "leaving land without releasing soil" and "releasing soil without releasing rights", and only a few farmers under the premise of compensation are willing to withdraw from the homestead and contracted land [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of relative deprivation on migration is more pronounced in male-headed households engaged in agriculture in rural areas [ 57 ]. Further research revealed that relative deprivation significantly and negatively affects rural residents' willingness to withdraw from homesteads [ 58 ]. However, to date, there has been little discussion of the effect of relative deprivation on rural residents' willingness to be cooperative members.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Su et al focused on the functional evolution and dynamic mechanism of homesteads, using the comprehensive index model evaluation method [36]. Furthermore, binary logistic models [37,38], structural equation models [39][40][41], and mediating effect models [42,43] are among the most common methodologies that scholars employ to explore farmers' willingness and behavior regarding withdrawing from rural homesteads from various angles. In terms of content, homestead withdrawal is a hot topic in current research.…”
Section: Introductionmentioning
confidence: 99%